MICROBIOLOGICAL STUDY OF BAUNG CATFISH (Mystus nemurus) ORIGINATING FROM PONDS, RIVER CAGES AND NATURAL CATCHES - Bella Kharisma; Bustari Hasan; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract This study was aimed to determine the microbiological quality of baung catfish (Mystus nemurus) originating from ponds, river cages and natural catches. The experimental method was used in this research with a non-factorial Randomized Completely Design consisting of 3 treatment levels, namely K (baung catfish originating from ponds), KS (baung catfish originating from river cages), and TA (baung catfish originating from natural catches). The parameters used were pH, total bacterial colonies, Salmonella sp, coliform and Escherichia coli bacteria. The results showed that the meat and belly of baung catfish obtained from ponds, river cages and natural catches affected the pH value and total bacterial colonies. Meanwhile for Salmonella sp and E. coli bacteria not found in meat and belly of baung catfish obtained from ponds, river cages and natural catches, whereas coliform bacteria not found in baung catfish meat obtained from natural catches. Keywords: Mystus nemurus, natural catches, ponds, river cages